2021
DOI: 10.3389/fphar.2021.635762
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside Improves Chronic Stress Induced Depressive Symptoms Through Microglial Activation Suppression

Abstract: Depression is a severe neurological disorder highly associated with chronic mental stress stimulation, which involves chronic inflammation and microglial activation in the central nervous system (CNS). Salidroside (SLDS) has been reported to exhibit anti-neuroinflammatory and protective properties on neurological diseases. However, the mechanism underlying the effect of SLDS on depressive symptoms has not been well elaborated. In the present study, the effects of SLDS on depressive behaviors and microglia acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 88 publications
(108 reference statements)
0
9
0
Order By: Relevance
“…Among them, Salidroside is widely studied. Sal (2-(4-hydroxyphenyl) ethyl-β-D-glucopyranoside) (Figure 2A) is a phenolic glycoside compound that is the main active ingredient extracted from Rhodiola Rose (Fan et al, 2021). It has potent pharmacological activities, mainly for preventing or treating disorders like neurodegenerative diseases, cerebral ischemia, fatigue, hypoxia, diabetes, and cancer (Grech-Baran et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Salidroside is widely studied. Sal (2-(4-hydroxyphenyl) ethyl-β-D-glucopyranoside) (Figure 2A) is a phenolic glycoside compound that is the main active ingredient extracted from Rhodiola Rose (Fan et al, 2021). It has potent pharmacological activities, mainly for preventing or treating disorders like neurodegenerative diseases, cerebral ischemia, fatigue, hypoxia, diabetes, and cancer (Grech-Baran et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…SMC can improve both sleep latency and duration, indicating a different mechanism from that of ramelteon. In mental assessment, OFT has been generally used to evaluate anxiety and spontaneous activity levels (Jin et al, 2019;, while FST is commonly used for depression and antidepressants screening (Petit-Demouliere et al, 2005;Fan et al, 2021). In the present study, significant differences appeared in FST rather than OFT, indicating the antidepressant effect of SMC and ramelteon.…”
Section: Discussionmentioning
confidence: 45%
“…Considering the interrelation between sleep deprivation and depression, we performed OFT to investigate if SMC improves mental behavior as previously described (Jin et al, 2019;. As evident from Figures 5C,D To verify the aforementioned findings, FST was also conducted to evaluate depressive-like behavior in rodents as previously described (Petit-Demouliere et al, 2005;Fan et al, 2021). Sleep-deprived mice exhibited longer forced swimming immobility time than the control group (p < 0.05), while treatment with ramelteon and three different doses of SMC exhibited significant improvement in the depressive-like behavior of mice (p < 0.05) (Figure 5E).…”
Section: Smc Improved Sleep and Depressive Symptoms In Sleep-deprived...mentioning
confidence: 93%
“…Clinical trials have demonstrated that salidroside can alleviate the symptoms of generalised anxiety, stress, and depression in humans (68-70). Preclinical studies have shown that salidroside exerts potent antidepressant-like effects in various animal models of depression and anxiety, including animal models of olfactory bulbectomy (OBX)-, chronic mild stress (CMS)-, and lipopolysaccharide (LPS)-induced depression and anxiety (54,63,64,71,72). Moreover, preclinical and clinical studies have con rmed that salidroside and the natural plant R. rosea are safer and have better e cacy than conventional antidepressants (62, 70,73).…”
Section: Salidroside Regulates Neurotransmitter Homeostasismentioning
confidence: 99%
“…Depression and anxiety are strongly associated with chronic stress exposure and social stimulation (86); the key pathogenic mechanisms of these disorders are chronic in ammation and microglial activation in the brain (87-89). Salidroside has been demonstrated to exert antineuroin ammatory effects and to prevent depression and anxiety (64,66,67,71,72,90,91). In CMS-, OBX-, or LPS-induced in ammation models, salidroside notably alleviates stress-induced hyperactivity and anxiety-like behaviours (66, 90,91), decreases immobility time and depression-like behaviours (66, 90), increases sucrose preference and locomotor activity (90), and decreases escape latency.…”
Section: Salidroside Ameliorates Neuroin Ammation and Pyroptosismentioning
confidence: 99%